The Pathogenesis-Related Maize Seed (PRms) Gene Plays a Role in Resistance to Aspergillus flavus Infection and Aflatoxin Contamination - Majumdar, Rajtilak; Rajasekaran, Kanniah; Sickler, Christine; Lebar, Matthew; Musungu, Bryan M.; Fakhoury, Ahmad M.; Payne, Gary A.; Geisler, Matt; Carter-Wientjes, Carol; Wei, Qijian; Bhatnagar, Deepak; Cary, Jeffrey W. (Frontiers in Plant Science, 2017)
Aspergillus flavus is an opportunistic plant pathogen that colonizes and produces the toxic and carcinogenic secondary metabolites, aflatoxins, in oil-rich crops such as maize (Zea mays ssp. mays L.). Pathogenesis-related proteins serve as an important defense mechanism against invading pathogens by conferring systemic acquired resistance (SAR) in plants. Among these, production of the pathogenesis-related maize seed protein, ZmPRms (AC205274.3_FG001), has been speculated to be involved in resistance to infection by A. flavus and other pathogens. To better understand the relative contribution of ZmPRms to A. flavus resistance and aflatoxin production, a seed-specific RNA interference (RNAi)-based gene silencing approach was used to develop transgenic maize lines expressing hairpin RNAs to target ZmPRms. Down-regulation of ZmPRms in transgenic kernels resulted in a ~250-350% increase in A. flavus infection accompanied by a ~4.5 to 7.5-fold higher accumulation of aflatoxins than control plants. Gene co-expression network analysis of RNA-seq data during the A. flavus-maize interaction identified ZmPRms as a network hub possibly responsible for regulating several downstream candidate genes associated with disease resistance and other biochemical functions. Expression analysis of these candidate genes in the ZmPRms-RNAi lines demonstrated down-regulation (vs. control) of a majority of these ZmPRms regulated genes during A. flavus infection. These results are consistent with a key role of ZmPRms in resistance to A. flavus infection and aflatoxin accumulation in maize kernels.